Modulation of Estrogen Response Element-Driven Gene Expressions and Cellular Proliferation with Polar Directions by Designer Transcription Regulators - Muyan, Mesut (PLoS One, 2015)
Estrogen receptor α (ERα), as a ligand-dependent transcription factor, mediates 17β-estradiol (E2) effects. ERα is a modular protein containing a DNA binding domain (DBD) and transcription activation domains (AD) located at the amino- and carboxyl-termini. The interaction of the E2-activated ERα dimer with estrogen response elements (EREs) of genes constitutes the initial step in the ERE-dependent signaling pathway necessary for alterations of cellular features. We previously constructed monomeric transcription activators, or monotransactivators, assembled from an engineered ERE-binding module (EBM) using the ERα-DBD and constitutively active ADs from other transcription factors. Monotransactivators modulated cell proliferation by activating and repressing ERE-driven gene expressions that simulate responses observed with E2-ERα. We reasoned here that integration of potent heterologous repression domains (RDs) into EBM could generate monotransrepressors that alter ERE-bearing gene expressions and cellular proliferation in directions opposite to those observed with E2-ERα or monotransactivators. Consistent with this, monotransrepressors suppressed reporter gene expressions that emulate the ERE-dependent signaling pathway. Moreover, a model monotransrepressor regulated DNA synthesis, cell cycle progression and proliferation of recombinant adenovirus infected ER-negative cells through decreasing as well as increasing gene expressions with polar directions compared with E2-ERα or monotransactivator. Our results indicate that an ‘activator’ or a ‘repressor’ possesses both transcription activating/enhancing and repressing/decreasing abilities within a chromatin context. Offering a protein engineering platform to alter signal pathway-specific gene expressions and cell growth, our approach could also be used for the development of tools for epigenetic modifications and for clinical interventions wherein multigenic de-regulations are an issue.